Clinical profile of patients with no-reperfusion therapy in Bosnia and Herzegovina and Serbia. (January 2014) - Trninic, Dijana; Dilic, Mirza; Vasiljevic, Zorana; Kulic, Mehmed; Srdić, Svetozar; Dobrijević, Neno; Sabanovic-Bajramovic, Nirvana; Begic, Alden; Kukavica, Nihad; Vukcevic, Vladan; Davidovic, Goran; Panic, Gordana; et al.
Abstract: There is little information about coronary reperfusion therapy patterns in patients with ST-elevation myocardial infarction (STEMI) in the former federal states of Yugoslavia. The objective of this study was to evaluate the clinical profile and mortality of patients who were hospitalized with a diagnosis of STEMI, but did not receive reperfusion therapy in Bosnia and Herzegovina and Serbia. This was an observational study using registry data from the International Survey of Acute Coronary Syndromes in Transitional Countries (ISACS-TC; ClinicalTrials.gov, NCT01218776) on 633 STEMI patients admitted to 14 hospitals in Bosnia and Herzegovina (both Republic Srpska and Federation of Bosnia and Herzegovina) and Serbia from October 2012 to September 2013. Of these, 61 (9.6%) received fibrinolytic therapy (Group A), almost exclusively with streptokinase (79.3%), 402 (63.5%) underwent primary percutaneous coronary intervention (PCI; Group B), and 170 (26.9%) received no-reperfusion therapy (Group C). In Groups A, B, and C, mean age was 60.3, 60.5, and 69.1 years, respectively. Patients in Group C were more likely to present after 12 h from symptoms onset (61.3 vs. 13.6% in Group A, and 13.4% in Group B). After adjustment for risk factors and clinical presentation, female sex, age, diabetes, prior MI, and symptom onset-to-presentation time after 12 h were all independent variables associated with no-reperfusion therapy. There was a significantly reduced in-hospital mortality in patients who received reperfusion therapy with fibrinolysis or primary PCI (odds ratio: 0.27, 95% confidence interval: 0.09–0.76, P = 0.01). The majority of STEMI patients from Bosnia and Herzegovina and Serbia undergo reperfusion therapy with fibrinolysis or primary PCI. More than one-fourth of the patients do not received any reperfusion therapy. Reperfusion therapies are applied to relatively lower risk patients. More elderly and diabetics should be considered for such strategies.